Reading Ezekiel 18 with the ancient versions - Van Rooy, H. F. (Journal for semitics, 2013)
Ezekiel 18 is one of the most important chapters in the book of Ezekiel. The chapter contains a number of textual problems, but the ancient versions, the Septuagint, Peshitta, Vulgate, and Targum can help the reader to solve these textual problems. The Septuagint demonstrates the existence of two textual traditions of Ezekiel. The Targum has a number of examples of the way in which this chapter was interpreted in a Jewish context. The Vulgate contains some indications of the interpretation of the text in an early Christian context. The Peshitta confirms many of the readings of the Masoretic Text against the Greek, but also demonstrates the way a translator transformed his text to simplify it for his readers.